Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2134/jeq2015.02.0096
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Isotope Variations to Trace Liming Input to Terrestrial Ecosystems: A Case Study in the Vosges Mountains

Abstract: Liming with Ca and Mg carbonates is commonly used to reduce soil and stream acidity and to improve vegetation growth and nutrition in forests. Ten years ago, dolomite lime was experimentally applied to a forest catchment on granite in the Vosges Mountains (northeast France), which is characterized by acid soils and drained by an acid stream. The average Mg isotope composition of the dolomite lime (-1.75‰) was low compared with that of tree foliage (-0.70‰), granite and deep soil layers (-0.40‰), and stream wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Because the difference in Mg isotopic signature between carbonate rocks and Mg pools in forest ecosystems is most often sufficiently big, the Mg released from the liming product can be traced in the ecosystem and its contribution to the different pools of Mg in the ecosystem can be quantified. * (Bedel 2015;Bizzarro et al 2005;Bolou-Bi et al 2016;Bolou-Bi et al 2009;Bolou-Bi et al 2012;Brenot et al 2008;De Villiers et al 2005;Kimmig et al 2018;Opfergelt et al 2014;Teng et al 2007;Wiechert & Halliday 2007;Young & Galy 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the difference in Mg isotopic signature between carbonate rocks and Mg pools in forest ecosystems is most often sufficiently big, the Mg released from the liming product can be traced in the ecosystem and its contribution to the different pools of Mg in the ecosystem can be quantified. * (Bedel 2015;Bizzarro et al 2005;Bolou-Bi et al 2016;Bolou-Bi et al 2009;Bolou-Bi et al 2012;Brenot et al 2008;De Villiers et al 2005;Kimmig et al 2018;Opfergelt et al 2014;Teng et al 2007;Wiechert & Halliday 2007;Young & Galy 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In forest ecosystems, the Mg pool in the organic layer originates mostly from leaf litter inputs and atmospheric inputs that are retained on the cationic exchange capacity of the organic layer(van der Heijden et al 2014). The δ 26 Mg values of atmospheric inputs ranges from -1.05 to -0.51‰(Bedel 2015;Bolou-Bi et al 2012;Pogge von Strandmann et al 2008;Tipper et al 2010) and was lower than the δ 26 Mg values of organic layers at all sites (except at Fougères).Furthermore, previous study in forest ecosystems highlight that leaf litter is slightly enriched in24 Mg compared to green leaves due to re-translocation of the foliar Mg during the growing season(Bedel 2015;Black et al 2007;Bolou-Bi et al 2016;Bolou-Bi et al 2012;Kimmig et al 2018;Kraj 2015;Matile 2000;Moynier & Fujii 2017), which would imply that the δ 26 Mg values of leaf litter at our four sites (not measured) was equal or below the measured foliar δ 26 Mg values. It would thus not be possible to obtain the δ 26 Mg values measured in the organic layer from the simple isotopic mixing of these two sources (i.e.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…with 7 M HCl) and AG50W‐X12 cation‐exchange resin (to eliminate major cations with 1 M HNO 3 ), as described by Bolou‐Bi and colleagues (2009). The efficiency of Mg separation from interfering cations was improved further by reducing the length of the column and changing both the acid used and its concentration (Bolou‐Bi et al ., ). Depending on the sample (mycelium or mineral substrate) Mg purification was achieved using either two or three purification stages and subsequently checking the molar ratio of the sum of all cations and Mg (Σ[cation]/Σ[Mg]) that was expected to be lower than 0.05 to avoid the effects of matrices and mass bias during the isotope ratio measurement (Galy et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The only study on agricultural soil so far by Gao et al (2018) reported increasing values of bulk soil δ 26 Mg with soil depth, from −0.85‰ in topsoil to −0.59‰ in soil at 100-cm depth, in a paddy soil developed from a latosol because of the decreasing Mg content retained on exchangeable sites. Similarly, soil management practices such as liming can also lead to differing δ 26 Mg values, particularly if the applied lime contains Mg of a different isotope composition from that found in the bulk soil, such as dolomite (Bolou-Bi et al, 2016). We hypothesize that differing isotope compositions of Mg in topsoil and subsoil can be used to evaluate the effect of soil managements on Mg uptake by crops.…”
Section: Highlightsmentioning
confidence: 99%